Роль і місце правоохоронних органів у правовій державі - Зайченко, В. В.; Лаптєва, А. В.; Zaychenko, V.; Lapteva, A. (КНТУ, 2013)
Стаття присвячена розгляду ролі і місця правоохоронних органів у правовій державі. Розкрито зміст діяльності правоохоронних органів у структурі державних органів, що спрямована на побудову правового демократичного суспільства, зміцнення правопорядку та законності, захист суспільства та особистості від порушень норм права. The purpose of this paper is to investigate issues related to the functioning of the police in a state of law, particularly in the area of human rights, freedoms and legitimate interests of man and citizen action using legal measures intended to maintain a stable law and order in the country, the fight against crime and other offenses. The article is devoted to the role and place of law enforcement in the state of law. The article deals with the problem of disclosure of the activity of law en- forcement bodies in the struct me of state organs, directed to the creation of a legal democratic society, strengthening of law and order, and legality, protecting the public and personality from the vi olation of rules of law. Unlike other systems of government, the system of law enforcement does not have the traditional organizational structure, such as the system of executive power, but a coherent set of systems forming factor which is not structural (organizational), and functional criteria - directly to law enforcement, that defined their common functionality, which is mainly in the protection and enforcement. Therefore, system-factor law enforcement is law enforcement, for which the state creates law enforcement.
Role and Place of Law Enforcement Agencies In Legal State
Keywords: правоохоронні органи; правова держава; правопорядок; законність; права і свободи людини; правоохоронна діяльність; законодавчий акт; правовий статус працівника міліції; police; rule of law; order; rule of law; human rights and freedoms; law enforcement; legislation; legal status of a police officer